Pengaruh Inflasi dan Tingkat Suku Bunga Terhadap Tingkat Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah di Indonesia - Sudirman, Sudirman; Fitrianti, Fitrianti (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2022)
This study aims to determine the effect of interest rates and inflation on the number of mudharabah deposits through the variable rate of profit sharing at Islamic commercial banks in Indonesia. This study was designed using a confirmatory approach. The data used is secondary data, the type of time series during the period 2011-2020. This study uses path analysis method with the help of software version 26. The results show that directly, inflation has a positive and significant effect on the amount of mudharabah deposit savings in Islamic banks in Indonesia by -0.462, interest rates have a positive and significant effect on the amount of mudharabah deposit savings in Islamic banks in Indonesia is 0.970, and the rate of profit sharing has a positive and significant effect on the amount of mudharabah savings deposits at Islamic banks in Indonesia of 0.251. Meanwhile, indirectly, inflation has a negative and insignificant effect on the amount of mudharabah deposit savings in Islamic banks in Indonesia; the interest rate has a positive and significant effect on the amount of mudharabah deposit savings in Islamic banks in Indonesia.